Optimalisasi Penerapan Sertifikasi Halal UMKM Halal Melalui Manajemen Supply Chain Management - Nasrun Baldah; Suhrowardi; Andi Suhandi; Bernad Hananto; Iin Masriah (JPPI: Jurnal Pengabdian Pelita Insani, 2025)
The Department of Cooperatives, Micro, Small and Medium Enterprises (MSMEs) in the Kedung Waringin District Government, Bekasi Regency is currently actively trying to develop business potential by collaborating with MSMEs. Many MSMEs in the Kedung Waringin District area are currently still using manual/traditional bookkeeping management and administration and many errors are still found in bookkeeping so that it is difficult for the supervisory board to carry out its supervisory function. The purpose of this community service is to provide comprehensive guidance and counseling to MSMEs in the Kedung Waringin District, Bekasi Regency, with the hope that MSMEs in the future will be able to compete both in terms of product quality produced and in service quality. The method used in implementing guidance with counseling and at the same time conducting training by applying entrepreneurial management training, financial management and marketing management to MSMEs in the Kedung Waringin District, Bekasi Regency. The results obtained after carrying out this training activity are that the MSMEs have been able to manage their businesses (entrepreneurial management), and know financial governance (financial management) by using applications to achieve zero errors, and the MSME participants can apply the training knowledge they have obtained in marketing management (administration) in developing quality products (turnover) and effective and efficient services.space.